Strategic Digital Capabilities and Business Growth in Digital-Native SMEs: A Conceptual and Empirical Exploration - Muhammad Wadud; Arifin Fajar Putera; Shinta Yunita; Marhamah; Panca Tuah Tuha (Global Research Collaboration, 2026)
The rapid expansion of the digital economy has transformed the business landscape of micro enterprises in Indonesia, particularly among digital-native home industries that operate entirely based on digital platforms from their inception. As the largest digital market in Southeast Asia, Indonesia has experienced a significant increase in technology adoption by small enterprises through social commerce platforms, online marketplaces, and digital payment systems. However, while prior studies have largely focused on the digital transformation of traditional SMEs, limited attention has been given to digital-native home industries, creating a gap in understanding the drivers of their business growth. This study aims to analyse the role of digitalisation in fostering business growth among digital-native home industries by integrating a conceptual model with preliminary empirical insights. A mixed exploratory design was employed, consisting of a structured literature review, a small-scale survey of 20 digital-native home industry owners, and semi-structured interviews with three key informants. The empirical component is intended to provide exploratory rather than confirmatory evidence. The findings suggest that digitalisation may contribute to expanded market access, improved operational efficiency, and increased revenue opportunities. However, business sustainability appears to depend not only on technology adoption but also on the development of dynamic digital capabilities, including data analytics utilisation, algorithm adaptation, and content-based marketing strategies.